The effect of fairy shrimp “branchoneta” (Dendrocephalus brasiliensis) as the initial diet of tambaqui postlarvae - Daltro, Aline da Cruz; Macedo, Carla Fernandes; Serafim-Junior , Moacyr; Brandão, Luan Lucas Leal; Gauthier, Nathália Byrro (Acta Scientiarum. Animal Sciences, 2021)
The effect of fairy shrimp “branchoneta” as the first exogenous feed for tambaqui postlarvae was evaluated. A hundred and eighty larvae were distributed in 12 aquariums, containing 1.5L of water and the stocking density was 10 larvae per liter. The trials lasted for 20 days and postlarvae were submitted to three diets (T1: Commercial feed, T2: branchoneta, and T3: Commercial feed with branchoneta), with a completely randomized design with four replicates for each treatment. During the trials, the water quality parameters were kept within ideal conditions for the species. The tambaqui postlarvae submitted to T2 and T3 showed better survival rates respectively. Regarding the postlarval development, larvae fed with only branchoneta had a better final weight (3.48 mg), daily weight gain (0.14 mg day-1), and the best specific growth rate (8.62%). The results also showed that the tambaqui postlarvae fed with only commercial feed developed less efficiently due to lower rates of survival and growth. The present study indicates that the branchoneta promoted greater development and survival rates of the tambaqui postlarvae and therefore, it presents good potential as a live food for the species.